Collaboration and Communication in Care at the Nursing Home: The Next of Kin’s Experiences of Participation Following Educational Intervention for Staff - Helene Åvik Persson; Birgitta Wallerstedt; Åsa Alftberg; Anna Sandgren; Gerd Ahlström (Nursing Reports)
Background: After an older person moves into a nursing home, the next of kin often continues to participate in the care provided there. This participation in care may contribute valuable knowledge of the preferences and wishes of the older person, thereby helping nursing staff deliver personalised care. Objectives: The aim of this study was to explore how next of kin experience their participation in the care of older persons residing in nursing homes after educating nursing staff about participation in palliative care. Methods: This follow-up study used a qualitative design based on semi-structured interviews with 37 next of kin. A thematic analysis was applied. Results: Participation of the next of kin involved active communication and collaboration with nursing staff, expressed in three themes: striving to achieve co-created care, navigating involvement through presence, and building commitment through communication and information. The dual role of being an emotionally close next of kin and a participant in the relative’s care was challenging and became increasingly burdensome and often overwhelming when the older person’s health deteriorated. Conclusions: This study reveals the need to develop and implement a policy for the participation of next of kin in the care of older people living in nursing homes. In addition, support groups can increase well-being through dialogue with other next of kin, thereby alleviating emotional strain. Increased implementation of life stories and the use of digital communication would keep the next of kin informed about the older person’s condition, especially when they cannot be present in person. Life story is a valuable tool for person-centred care and strengthens the relationships between the next of kin, the older person, and the nursing staff.